POLLUTION AND ITS EFFECT ON DEWAS ENVIRONMENT - Mehta, Rekha (International Journal of Research -GRANTHAALAYAH, 2015)
From the age old period, man & environment have been an integral part each other. Over the years hence has been a spreading of environmental consciousness. The current focus on environment is not new is it has been a part of Indian culture for a long time. But various change have a shock the balance both human life & environment. One of the major the environment is water pollution. The main source of water pollution are sewage, increasingpollution density,dumping of agriculture of and industrial waste reduce flow of water in to lakes due to withdrawal for irrigation and cultivation and inversion of idols during festivals. Fresh water lakes, river & ground water get contaminated and in turn, there is storage in the supply of drinking water crop get infected. People contract diseases like, dysentery, indigestion,skin irritation which some times proves fatal.